2014
DOI: 10.1038/jid.2014.5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants of the IL22 Promoter Associate to Onset of Psoriasis before Puberty and Increased IL-22 Production in T Cells

Abstract: Most psoriasis susceptibility genes were identified in cohorts of mixed clinical phenotypes and the exploration of genes in clinical subtypes is scarce. IL-22 has an established role in host defense and in psoriasis skin pathology, reflecting the delicate balance between control of infection and immunopathology. In a case-control study, we compared the genetic association to IL22 in psoriasis onset in patients between 0-9 (n=207), 10-20 (n=394), and 21-40 (n=468) years with healthy controls (n=1,529). Logistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 47 publications
0
43
1
Order By: Relevance
“…Previous studies from our group using puberty as cut-off indicate differences in the genetic background between pre-pubertal and pubertal children with a stronger association to HLA-C*06 in pubertal children (20,21). In contrast to the findings of Gudjonsson et al (22) a younger age of onset was not associated with more severe disease (higher PASI) in our material (see Table II).…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Previous studies from our group using puberty as cut-off indicate differences in the genetic background between pre-pubertal and pubertal children with a stronger association to HLA-C*06 in pubertal children (20,21). In contrast to the findings of Gudjonsson et al (22) a younger age of onset was not associated with more severe disease (higher PASI) in our material (see Table II).…”
Section: Discussioncontrasting
confidence: 85%
“…However, most studies are retrospective and reliable information captured at onset is lacking. We have previously reported that psoriasis onset before puberty is genetically distinct from adolescent onset (20,21). The overall aim of this study was to examine whether such differences would translate into phenotypic differences and indeed, we found that depending on the age of onset, the clinical disease presentation displayed significant variations.…”
mentioning
confidence: 94%
“…Polymorphisms in the IL-22 gene have been associated with psoriasis in a Japanese population (289) and a polymorphism in the promoter region of IL-22 is associated with increased production of IL-22 and increased risk of psoriasis onset in childhood (290). In addition, copy number variation of IL-22 gene exon1 was significantly associated with psoriasis severity (291).…”
Section: ) Target Tissues: Pathophysiology and Regenerative Biologymentioning
confidence: 99%
“…IL-22 induces epidermal hyperplasia [77] but not keratinocyte proliferation [81]; it inhibits epidermal differentiation and, either alone or in synergy with IL-1 and IL-17, drives the induction of pro-inflammatory gene expression [77,81]. Interestingly, a genetic variant that increases activity at the IL22 promoter has been associated with childhood-onset psoriasis [82]. Thus both genetic and functional data support the view that IL-22 is another critical cytokine in the pathogenesis of psoriasis and as such is a target of drug development [8].…”
Section: The Il-10 Family: Sheep In Wolves’ Clothing?mentioning
confidence: 99%